De grafos a emparelhamentos : uma possibilidade viável de encantar-se com a matemática - Ferreira, Verônica Craveiro de Santana (2014)
This thesis aims to show that the theory of graphs, especially matching, can be studied in high school and gradually as the implementation of this theory in the classroom can foster in students interest in mathematics. Thus, this paper aims to demystify the idea that mathematics content ends with high school approaching students the theories recently developed in academy. The graph theory is considered an e cient tool to solve problems in various areas. There are numerous situations that can be modeled by that enable develop a range of skills, so it becomes so appealing to anyone who comes into contact with it. For the development of this thesis began our study addressing basic concepts of graph theory useful for understanding this work then present some problems that can be worked in high school and nalized with a speci c topic of this theory, matchings, with many applications that can be modeled as contextualized and practical problems of everyday life.